Johannes Justus Rein - Hohmann, Joseph (ERDKUNDE, 1968)
Johannes Justus Rein, author of the first modern scientific study of Japan, was Richthofen's successor in the Chair of Geography at Bonn, and held it for 27 years. Born in Raunheim on the Main on 27th January 1835, Rein became a schoolteacher on completion of his studies and was active in the Senckenberg Nature Research Society in Frankfurt. He spent two years as tutor in the household of the Governer of the Bermuda Islands. A research trip in the service of the Prussian government took him to Japan in the years 1873-75. Apart from a series of individual publications, the fruit of these researches was his life-work 'Japan, from travel and study' which appeared in two large volumes in 1881 and 1886, almost immediately appearing in an English translation. Rein taught in Marburg from 1876 to 1883. As Professor of Geography in Bonn, he encompassed from 1883 to 1910 a multi-faceted and successful teaching career. In addition, he accepted a Chair of Commodities at the newly founded Trade High School in Cologne. Major journeys took him to Spain, Morocco, the USA, Canada and Russian Turkestan and the scientific results were reflected in an impressive number of publications and lectures. Rein was a Corresponding Honorary Member of the Royal Geographical Society of London and the Japan Society of London. He died in Bonn on 23rd January 1918, aged almost 83.